Sleep Problems and Workplace Violence: A Systematic Review and Meta-Analysis - Magnavita, Nicola; Di Stasio, Enrico; Capitanelli, Ilaria; Lops, Erika Alessandra; Chirico, Francesco; Garbarino, Sergio (Frontiers in Neuroscience, 2019)
Background: This systematic review with meta-analysis was carried out to study the relationship between workplace violence and sleep problems. Methods: The PRISMA statement was used to conduct a systematic search of the literature on PubMed/MEDLINE, Scopus, Sociological abstract, DOAJ, Web of Science, and Google Scholar databases. Of the original number of 749 studies, 34 were included in the systematic review, and 7 in the meta-analysis. Results: A total of 119,361 participants from 15 different countries took part in these studies which were published between 1999 and 2019. Significant heterogeneity was observed among the studies (I2 = 96%). In a random-effects meta-analysis model, pooled odds ratio (OR) analysis revealed that there was a direct relationship between occupational exposure to violence and sleep problems (OR = 2.55; 95% CI = 1.77–3.66). According to the GRADE guidelines, the quality of evidence of the association was low. Conclusions: The findings of this study demonstrate that occupational exposure to physical, verbal, or sexual violence is associated with sleep problems. Further research on the relationship between violence and sleep is needed so that appropriate measures can be taken to prevent violence and improve sleep hygiene in the workplace. Trial Registration Number: PROSPERO International prospective register of systematic reviews (CRD42019124903) February 9, 2019.